Comparison of the Effectiveness of Imago Therapy and Schema Therapy on Executive Functions in Students with Academic Burnout - Karimiabadeh, Leila; Bigdeli, Hossein; Ahmadi Tahour Soltani, Mohsen (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to compare the effectiveness of Imago therapy and schema therapy in improving executive functions among university students experiencing academic burnout. Methods and Materials: The research employed a quasi-experimental design with a pretest–posttest–follow-up structure and a control group. The statistical population consisted of undergraduate students from Shiraz Nonprofit University during the 2024–2025 academic year who met the criteria for academic burnout. Forty-five students were selected using convenience sampling and randomly assigned to three groups: two experimental groups (Imago therapy and schema therapy) and one control group, each comprising 15 participants. The experimental groups received Imago therapy (seven 120-minute modules) and schema therapy (eight 90-minute sessions), while the control group received no intervention. Data were collected at three stages—pretest, posttest, and follow-up—using the Academic Burnout Questionnaire and the Behavior Rating Inventory of Executive Function–Adult Version (BRIEF-A). Data analysis was performed using repeated measures analysis of variance (ANOVA) and Bonferroni post hoc tests with SPSS version 25. Findings: The results demonstrated that both therapeutic interventions led to statistically significant improvements in executive functions—including working memory, cognitive flexibility, and response inhibition—compared with the control group (p < .001). Additionally, Imago therapy showed significantly greater effectiveness than schema therapy in both the posttest and follow-up stages (F(4,114) = 12.021, p < .001, η² = .297). Conclusion: These findings highlight the importance of relationship-based and reflective interventions in improving cognitive regulation and reducing academic burnout.